Cartoon Network. Christmas rocks - Warner Home Video (Firm) (Burbank, CA : Warner Home Entertainment, 2005)
Five Cartoon Network Christmas episodes.
Ed, Edd 'n Eddy. Jingle jingle jangle -- Dexter's Laboratory. Dexter vs. Santa's claws -- Courage, the Cowardly Dog. The snowman cometh -- I A.M. Weasel. Happy baboon holidays -- Johnny Bravo. Twas the night -- Powerpuff Girls. Mime for a change -- Grim Adventures of Billy & Mandy. Battle of the bands -- Codename: Kids Next Door. Operation: P.I.A.N.O.
MPAA rating: Not rated.
DVD; Dolby digital stereo.
English dialogue, English, French or Spanish subtitles; closed-captioned.
CPL-MAIN EU-MAIN SA-MAIN SH-MAIN SH-WOODS TW-MAIN MML-MAIN WE-WY
Keywords: Christmas -- Juvenile drama; Holidays -- Juvenile drama; DVD-Video discs -- 2005.; Children's films -- 2005.; Video recordings for the hearing impaired -- 2005.